Integration of Theory of Planned Behavior and Value-Attitude-Behavior as a Basis for Decision Making in Selecting Event Organizer Services - Puspitasari, Ika; Roostika, Raden Roro Ratna (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The post-Covid-19 pandemic Event Organizer (EO) business has shown rapid recovery and growth as part of the MICE sector. Amid the increasingly fierce competition in the EO business, understanding the factors that influence client loyalty is crucial for business continuity, but research integrating TPB and VAB in this context is still very limited. This study aims to analyze the influence of subjective norms, attitudes, and quality on client loyalty in the decision to choose event organizer services. The research method uses a quantitative approach with data collection techniques through online questionnaires. The sampling technique used purposive sampling on EO service client respondents in Jayapura City and surrounding areas, and the data were analyzed using SPSS software. The results showed that subjective norms have a significant effect on loyalty, attitudes have a significant effect on loyalty, and quality has a significant effect on loyalty. These findings confirm the relevance of TPB and VAB in the context of the MICE industry, and provide practical implications for EO business people in developing effective marketing strategies to increase client loyalty.